A novel microbial biofilm carrier for wastewater remediation - Al-Amshawee, Sajjad; Mohd Yusri, Mohd Yunus; A. A., Azoddein (IOP Publishing, 2020)
Biological wastewater treatment via biofilm colonies are still in their early stages of evolution. Solid carriers made of wide range of materials in different designs have been introduced to increase biofilm growth by delivering high surface area which expands microbes’ attachment. It reduces 70-90% of total wastewater contamination (Based on the treatment circumstances and influent properties). In addition, it is considered a low-cost biological process and highly preferred by wastewater industries. Despite that, biofilm carriers failed to deliver a stable biotreatment. Unsteady bioremediation could occur because of using ineffective designed carrier which disturbs the microbial growth. Numerous biofilm carriers had been reviewed and mentioned in this paper like K1, AMT, BioBall, …etc. Then, two carrier designs named as Ultra and Micro media were introduced to carry and protect biofilm and microbial colonies from being removed during the process. Its expected that the new biofilm carriers can improve moving bed biofilm reactor (MBBR) performance in terms of stability, biomass accumulation, clogging, and biofilm growth. At the end, unharmful wastewater can be discharged to the waterways or recycled back into the industry. Finally, this study suggests designing carriers having crimped surfaces to enhance the extracellular polymeric substance attachment.